THE ROLE OF INCLUSIVE LEADERSHIP IN ENHANCING TALENT RETENTION AMONG REMOTE WORKFORCE: A MULTINATIONAL STUDY - Purnama, Kusna Djati; Wardi, Agustinus; Aditya, Galuh (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The transformation of the workplace in the digital era has pushed organizations to adopt more adaptive and inclusive leadership styles, particularly in managing and retaining talent. Inclusive leadership is believed to foster a psychologically safe work environment, build trust, and enhance employee engagement—key factors influencing talent retention decisions. This study aims to examine the impact of inclusive leadership on talent retention, by exploring the mediating roles of psychological safety, trust, and employee engagement. A quantitative approach was employed through an online survey involving 150 respondents from the professional and technology sectors. Data analysis was conducted using multiple linear regression and Structural Equation Modeling (SEM) with the support of SPSS and SmartPLS. The findings reveal that inclusive leadership significantly influences talent retention, both directly and indirectly through the three mediating variables. These results highlight the importance of leadership styles that are attuned to employees’ psychological needs. Theoretically, this study contributes to the growing body of literature on leadership and employee retention. Practically, it offers strategic recommendations for organizations to develop sustainable human resource management policies focused on employee well-being—particularly in the context of an increasingly digital and flexible work environment.